FREQUENCY OF DIABETIC RETINOPATHY IN PATIENTS AFTER TEN YEARS OF DIAGNOSIS OF TYPE 2 DIABETES MELLITUS - Shaikh, Mumtaz Ali; Gillani, Saima; Yakta, Dur -E- (Journal of Ayub Medical College Abbottabad, 2010)
Background: Diabetic retinopathy is one of the most common and serious complications of type 2 diabetes mellitus and a leading cause of blindness not only in Pakistan but also worldwide. So we conducted this study to record the frequency of diabetic retinopathy in known diabetic patients ten years after diagnosis of type 2 diabetes mellitus. Methods: The study was conducted at Liaquat University of Medical and Health Sciences, Jamshoro, Pakistan for a period of 1 year from January 2008 to January 2010. The study group comprised of 200 patients of type 2 diabetes mellitus attending the medical clinic. All patients who were diagnosed as type 2 diabetes mellitus since ten years duration were included in the study. Retinopathy was graded into background, pre proliferative and proliferative retinopathy. Type 2 diabetes was diagnosed using the WHO criteria. Statistical analysis was carried out using the SPSS-11. Results: Diabetic retinopathy was found in 25.5% of the total Type 2 patients after ten years of diagnosis, and of these 4% of patients had proliferative retinopathy. Conclusion: Type 2 diabetic patients should be screened as early as possible to prevent permanent visual loss by timely management of diabetic retinopathy because diabetes is one of most common preventable cause of blindness in the world. Keywords: Retinopathy, Type 2 Diabetes